Institutional quality, income level, and debt sustainability: new evidence using dynamic panel threshold regression - Lee, Chee Loong; Ahmad, Riayati; Karim, Zulkefly Abdul; Khalid, Norlin (Technological and Economic Development of Economy, 2023)
Most countries have suffered from prolonged budget deficits over the past two decades. This situation has made researchers and policymakers aware of the challenges to debt sustainability. This study investigates the threshold effect of institutional quality on debt sustainability in a panel of 82 countries, focussing on various threshold effects at different income levels. All the countries selected for this study fell under the categories of high income (HI), upper middle income (UMI), and lower-middle and low income (LMLI) based on the World Bank classifications. The dynamic threshold panel regression results indicate the presence of a threshold effect of institutional quality on the fiscal reaction function (including debt sustainability and cyclical fiscal policy) in all the countries with different income levels. In HI countries, fiscal adjustment weakens if institutional quality surpasses the threshold value of institutional quality. The fiscal adjustment in UMI countries is similar to that in HI countries but statistically insignificant. By contrast, governments in LMLI countries can promote sustainable debt if their institutional quality exceeds the threshold value. Thus, policymakers in LMLI countries need to prioritise their efforts to raise the level of institutional quality to promote debt sustainability.